2008
DOI: 10.2136/vzj2007.0172
|View full text |Cite
|
Sign up to set email alerts
|

Gravity‐Driven and Viscosity‐Dominated Infiltration into a Full‐Scale Sand Model

Abstract: Data from an infiltration and drainage experiment into and from a sand tank model of 5 by 3 m and 2 m deep were reevaluated. The uniform sand overlaid a 0.2‐m‐thick gravel layer from which five perforated pipes collected drainage flow. The data include time series of capillary potentials, ψ, volumetric water contents, θ, both from nine levels, and drainage flow, q, that resulted from sprinkler infiltration with a constant rate of 15.6 mm h−1 that lasted >16 h. The wetting and the pressure fronts (i.e., the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…There are indications that viscous flow is rather tolerant on permeable‐media lengths. The applicability of viscous flow to infiltration and drainage has been demonstrated in numerous cases, ranging from the submillimeter to the meter scale (see, for instance, Hincapié and Germann, 2009c; Germann and al Hagrey, 2008). Moreover, Dubois (1991) reported approximate wetting front velocities of v = 2 × 10 −4 m s −1 in crystalline rocks of the Mont Blanc massif in the three‐corner region of France, Italy, and Switzerland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are indications that viscous flow is rather tolerant on permeable‐media lengths. The applicability of viscous flow to infiltration and drainage has been demonstrated in numerous cases, ranging from the submillimeter to the meter scale (see, for instance, Hincapié and Germann, 2009c; Germann and al Hagrey, 2008). Moreover, Dubois (1991) reported approximate wetting front velocities of v = 2 × 10 −4 m s −1 in crystalline rocks of the Mont Blanc massif in the three‐corner region of France, Italy, and Switzerland.…”
Section: Discussionmentioning
confidence: 99%
“…Further, no trend with depth of the gradual increases in θ( Z m , t ) from θ in to θ max was discernible. Thus, Germann and al Hagrey (2008) concluded that the gradual increase was due to local processes most likely occurring within the control volume of the TDR probes. Germann (2014) provided additional clues on the gradual increase of θ( Z m , t ).…”
Section: Methodsmentioning
confidence: 99%
“…According to Germann and al Hagrey (2008), the wcw's average wetting front velocity from the soil surface to depth …”
Section: Statistical Analysesmentioning
confidence: 99%
“…Thus, constant v ac during infiltration indicates constant rigidity of the medium, even under increasing water contents. Moreover, ψ may have approached atmospheric pressure, as Germann and al Hagrey () reported from the Kiel sand tank during infiltration. In conclusion, there was no impact of antecedent ψ on early infiltration whereas water moved freely.…”
Section: Preferential Flow's Independence From Capillaritymentioning
confidence: 86%